Gametogenesis of pacific salmon. 2. Chum salmon Oncorhynchus keta - O. V. Zelennikov (Известия ТИНРО)
All available information on gametogenesis of chum salmon Oncorhynchus keta cited in scientific literature is summarized. The phases of indifferent development and sex differentiation are overviewed, specific features of the testes and ovaries development are noted, forming of fecundity is analyzed.